Sex-specific post-translational regulation of the gamete fusogen GCS1 in the isogamous volvocine alga Gonium pectorale - Kawai-Toyooka, Hiroko; Mori, Toshiyuki; Hamaji, Takashi; Suzuki, Masahiro; Olson, Bradley J.; Uemura, Tomohiro; Ueda, Takashi; Nakano, Akihiko; Toyoda, Atsushi; Fujiyama, Asao; Nozaki, Hisayoshi (My University, 2014)
Male and female, generally defined based on differences in gamete size and motility, likely have multiple independent origins, appearing to have evolved from isogamous organisms in various eukaryotic lineages. Recent studies of the gamete fusogen GCS1/HAP2 indicate that this protein is deeply conserved across eukaryotes, and its exclusive and/or functional expression generally resides in males or in male homologues. However, little is known regarding the conserved or primitive molecular traits of males and females within eukaryotes. Here, using morphologically indistinguishable isogametes of the colonial volvocine Gonium pectorale, we demonstrated that GCS1 is differently regulated between the sexes. G. pectorale GCS1 molecules in one sex (homologous to “male”) are transported from the gamete cytoplasm to the protruded fusion site, whereas those of the other sex (“females”) are quickly degraded within the cytoplasm upon gamete activation. This molecular trait difference might be conserved across various eukaryotic lineages and may represent male and female prototypes originating from a common eukaryotic ancestor.
Keywords: Gamete fusogen GCS1/HAP2; Eukaryotes; Isogametes; Gonium pectorale; GCS1